Projeto e desenvolvimento de uma plataforma automatizável para sensor baseado na ressonância de plasmons de superfície - Silva, Francisco Josiran da (Universidade Federal Rural do Semi-Árido, 2021)
Biological event detection systems are essential for understanding and monitoring molecular interactions. Among the detection technologies, commonly used, those based on Surface Plasmon Resonance (SPR) stand out due to their high sensitivity. The instrumentation of SPR sensors requires optical, electronic, fluidic and mechanical components, carefully positioned for the correct excitation of the phenomenon. These components are normally rearranged in fixed positions. Any adjustments are made manually, in order to adjust the sensor so that they always work in the same condition of use. In addition, many sensors have bulky instrumentation and expensive procedures, requiring well-trained operators and advanced laboratory infrastructure for component adjustments. The PPBIO biochip makes it possible to develop SPR sensors in a practical, less complex way, avoiding the need for rotational mechanical elements. However, the structures for this biochip are also based on components with fixed positions. This work seeks to perform faster analysis in relation to the mechanical platform, optimizing data processing and acquisition. The results obtained, through the analysis between the theoretical and experimental curve, allowed to conclude that the more accentuated and deep the SPR curve, the better optical coupling and, consequently, the better the SPR phenomenon. They made it possible to analyze the width of the SPR curve, concluding that the more pronounced, the greater the detection precision and the better optical coupling; and the smaller the width, the better the sensitivity, consequently, the better the SPR phenomenon. Thus, the automated platform, as a scientific contribution, has application to operate in the angular interrogation mode, as it provides a better alignment of the optical coupling. Having one of the advantages of the platform, the temperature control, able to avoid slight distortions in the optical path
Keywords: PPBIO; Sensor óptico; Ressonância de Plasmons de Superfície; Instrumentação eletrônica; Surface Plasmons Resonance; Optical sensor; ENGENHARIAS::ENGENHARIA ELETRICA